2019
DOI: 10.1002/cctc.201901567
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Redox Dynamics of Vanadium Species Impregnated in Layered Siliceous Zeolitic Structures during Methanol Oxidation Reactions

Abstract: Supported transition metal catalysts have been extensively applied to oxidative and reductive processes. The understanding of surface speciation and active site‐support interactions in these materials play a substantial role in developing improved heterogeneous catalysts. Herein, a series of impregnated 3D ferrierite and 2D ITQ‐6 siliceous supports with variable loading of vanadium oxide was prepared. Chemical and structural properties of the materials were studied by X‐ray diffraction, N2 physisorption, induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…Wu et al 22 investigated supported VO x /Al 2 O 3 catalyst after exposure to methanol with XPS under UHV conditions and detected V 3+ and V 4+ species. Vieira et al 19 investigated zeolite-supported vanadia catalysts in the methanol ODH by in situ time-resolved V K-edge XAS and concluded that V 4+ is the main intermediate involved in the reaction. The observed rate of V 4+ reoxidation by oxygen, however, was slower than V 5+ reduction by methanol, which contradicts the literature and might be related to the large volume of the in situ cell, which is not ideal for kinetic studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al 22 investigated supported VO x /Al 2 O 3 catalyst after exposure to methanol with XPS under UHV conditions and detected V 3+ and V 4+ species. Vieira et al 19 investigated zeolite-supported vanadia catalysts in the methanol ODH by in situ time-resolved V K-edge XAS and concluded that V 4+ is the main intermediate involved in the reaction. The observed rate of V 4+ reoxidation by oxygen, however, was slower than V 5+ reduction by methanol, which contradicts the literature and might be related to the large volume of the in situ cell, which is not ideal for kinetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…12−14 The oxidation of the partially reduced metal intermediate (M (x−n)+ ) by molecular oxygen (Step 2 in Scheme 1) is assumed to be very rapid 8,9,12,15,16 and, therefore, the concentration of the M (x−n)+ intermediate during the ODH process should be low. The mechanism of alcohol oxidation over supported VO x species was examined by many groups using multiple in situ spectroscopic techniques (Fourier transform infrared (FT-IR) spectroscopy, 2,9,15−19 Raman spectroscopy, 11,18,20 diffuse reflectance UV−vis (DR UV−vis) spectroscopy, 18,20 X-ray photoelectron spectroscopy (XPS), 9,15,17 and X-ray absorption spectroscopy (XAS) 19,21 ). Although several reaction mechanisms were proposed based on the nature of the observed surface reaction intermediates, the redox activity of vanadium and titanium species is difficult to assess under operando conditions and in a quantitative manner.…”
Section: ■ Introductionmentioning
confidence: 99%
“…59 At the 2-D monolayer, polyvanadates resemble the surface of crystalline domains with trigonal bipyramidal environments. These three structures and their coexistence have been previously probed with the following: Raman spectroscopy, where Raman band shifts for the V�O features (1008 to 1031 cm −1 ) and the emergence of broad V−O−V features (600−1000 cm −1 ) indicate the structural transition of supported VO x from predominantly monomeric to polymeric domains; 37,40,60 X-ray adsorption, where measured coordination shells and bond lengths were used to define the structures of VO x domains on ferrierite-type zeolites; 61 and high-resolution transmission electron microscopy, where above the 2-D monolayer VO x loading, the formation of overlayers in conjunction with bulk crystallite clusters was imaged for VO x supported on anatase TiO 2 . 36 To quantify the surface densities ρ s of VO x domains and the lattice oxygen atoms, we first define the footprint of the various VO x domains dispersed on the surface.…”
Section: Quantification Of the Active Vomentioning
confidence: 99%
“…The redox dynamics of V impregnated into 3D Ferrierite and 2D ITQ-6 siliceous supports with 1-10 wt% V were investigated by Vieira et al [176], who found that dispersion and stabilization of V oxides were improved by isolated silanol groups on the surface before impregnation. XRD, XAS, and DR-UV-Vis spectroscopy identified V to be highly dispersed at 1 wt% and 5 wt% V in Si-ITQ-6 with monomeric and polymeric species or oxide clusters while 10 wt% in Si-ITQ-6 and Si-FER showed formation V 2 O 5 clusters on the surface.…”
Section: •+mentioning
confidence: 99%
“…EXAFS and XANES showed complete reduction of V 5+ to V 4+ and back by isothermal periods of non-oxidizing atmosphere followed by regeneration with O 2 . All V species were concluded to be active in the oxidation of MeOH albeit with different rates due to differences in the V 5+ /V 4+ equilibrium under oxidant conditions as reoxidation was limited [176]. In a study by Zhang et al [177] on co-electrospun VtiO x hollow nanofibers, a yield of 90% MF was reached at 150 • C and was attributed to a high surface content of V 4+ [177].…”
Section: •+mentioning
confidence: 99%